Disaster Communication and Institutional Coordination in Urban Flood Management: A Case Study of Medan City - Nuraflah, Cut Alma (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
Flooding in Medan City has had extensive social, economic, and psychological impacts on local communities, affecting tens of thousands of residents through damage to property, infrastructure loss, and prolonged trauma. These recurrent floods are largely attributable to Medan’s geographical characteristics, particularly the presence of numerous active rivers that increase hydrometeorological vulnerability. Consequently, residents are required to coexist with disaster risks, placing the Regional Disaster Management Agency (BPBD) at the forefront of flood response and mitigation efforts. This study aims to examine BPBD Medan City’s flood management strategies, its communication and coordination practices during disaster response, and the key obstacles encountered in the disaster management process. Using a disaster communication perspective grounded in Haddow’s framework, this research focuses on five dimensions: audience focus, leadership commitment, situational awareness, the role of media, and disaster communication planning. Data were collected through semi-structured interviews with nine key informants selected via purposive sampling, all of whom held strategic roles and had direct experience in flood disaster management. The data were analysed using the Miles and Huberman interactive model, involving data reduction, thematic categorisation, interpretation, and verification. The findings reveal that BPBD Medan City continues to implement flood mitigation within a regional autonomy paradigm, resulting in the absence of a comprehensive and strategic approach to hydrometeorological flood management. Disaster coordination remains highly centralised, with strong sectoral egos persisting across institutions and creating significant coordination gaps. BPBD also faces structural constraints, inter-agency communication barriers, and complex community dynamics, including unresolved trauma among flood victims. This study concludes that effective disaster management in Medan City requires improvements in three key areas: systematic disaster communication planning, strengthened inter-institutional coordination, and enhanced citizen participation in disaster mitigation efforts.